Strategi Guru PAI Dalam Memotivasi Belajar Peserta Didik di Madrasah Aliyah Negeri - Muammar Qadafi; Awaludin Parhera (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
Learning activities are often found that students do not have motivation in learning, this problem is caused by a teacher not paying attention to students, not getting used to reprimanding with spontaneity when seeing students not excited in learning activities, a teacher is not able to pack interesting lessons so that students easily feel bored so that students do not carry out tasks and teacher commands, This research uses descriptive qualitative with Miles and Huberman's interactive data analysis by means of data collection, data presentation, data reduction and verification or drawing conclusions, so that the results of this study students are really interested in participating in Islamic Religious Education lessons with reflective learning strategies by providing incentives and giving praise, gifts, numbers and providing punishments.